High‐grade myelodysplastic syndrome in a pediatric multi‐organ transplant recipient: A case report and literature review. (10th April 2022) - Owens, Trudie J.; Patel, Sachit A.; Greiner, Timothy C.; Cannatella, Jeffrey J.; Grant, Wendy J.; Langnas, Alan N.; Vo, Hanh D.
Abstract: Background: Pediatric myelodysplastic syndrome is a rare but life‐threatening condition requiring prompt recognition and management. Methods: We herein present the only reported case of a pediatric multi‐organ transplant recipient developing myelodysplastic syndrome. Results: The patient was a 14‐year‐old girl on chronic calcineurin inhibitor therapy who presented with peri‐rectal pain approximately 13 years after liver, small bowel, and pancreas transplant. The initial workup revealed pancytopenia and parvovirus B19 viremia. Her definitive diagnosis was complicated by a lack of adequate bone marrow biopsy specimens and expert consultation that resulted in treatment for hemophagocytic lymphohistiocytosis. She was later diagnosed with high‐grade myelodysplastic syndrome. Although curative treatment with chemotherapy and hematopoietic stem cell transplantation was strongly considered, it was not performed due to the child's rapid clinical progression, ventilator status, and active infections. The patient died approximately 6 months following symptom onset. Conclusions: This case emphasizes the importance of early recognition of myelodysplastic syndrome in multi‐organ transplant recipients on chronic immunosuppression. Pancytopenia is a common presentation in the post‐transplant period that requires thorough investigation. Multiple confounding considerations such as infection, immunosuppression, and systemic inflammation can delay the diagnosis of underlying hematological malignancies. Transplant care providers should be aware of myelodysplastic syndrome and advocate for a comprehensive evaluation, given early recognition and intervention can significantly improve outcomes.